Most dangerous : Daniel Ellsberg and the secret history of the Vietnam War - Sheinkin, Steve (Square Fish/Roaring Brook Press, 2019)
Highlights seven years in Daniel Ellsberg's life when he went from being a trusted government insider to being declared "the most dangerous man in America." Examines the events surrounding Ellsberg's exposure of the Pentagon Papers, a 7,000-page document that uncovered the secret history of the Vietnam War that would forever change the relationship between American citizens and the government officials they put their faith in to represent their interests.